Experimental and numerical study of the effects of acoustic sound absorbers on the cooling performance of Thermally Active Building Systems. (1st May 2017) - Domínguez, L. Marcos; Kazanci, Ongun B.; Rage, Nils; Olesen, Bjarne W.
Abstract: Free-hanging horizontal and vertical sound absorbers are commonly used in buildings for room acoustic control; however, when these sound absorbers are used in combination with Thermally Active Building Systems, they will decrease the cooling performance of Thermally Active Building Systems and this will affect the thermal indoor environment in that space. Therefore, it is crucial to be able to quantify and model these effects in the design phase. This study quantifies experimentally the effects of horizontal and vertical free-hanging sound absorbers on the cooling performance of Thermally Active Building Systems and on the thermal indoor environment. The experiments were carried out in a climate chamber configured as a two-person office room. Different ceiling coverage ratios were tested. In addition, a commercially available dynamic building simulation software was used with a recently developed plug-in for acoustic elements, which allows modeling free-hanging horizontal sound absorbers that partially cover the ceiling. With horizontal sound absorbers, the cooling performance of the Thermally Active Building System decreased by 11%, 23% and 36% for ceiling coverage ratios of 43%, 60% and 80%, respectively. With vertical sound absorbers, the decrease in cooling performance was 8%, 12%, and 14% for the corresponding cases, respectively. The numerical model predicted closely the cooling performance reduction, air temperatures and ceiling surface temperatures in most cases, while there were differences in mean radiant temperatures and cooling capacity coefficients, indicating that the model can be improved in certain aspects. Highlights: Effects of free-hanging sound absorbers on TABS cooling performance were studied. Different ceiling coverage ratios with horizontal and vertical panels were studied. Experimental and dynamic building simulation results are presented. TABS cooling reduced by 11%, 23% and 36% for 43%, 60% and 80% ceiling coverage. TABS cooling reduced by 8%, 12%, and 14% for similar cases with vertical panels.